Offering Oncology Services in a municipality of Minas Gerais, Brazil - Felipe Ribeiro, Jefferson; de Oliveira Rodrigues, Dennis; de Oliveira Faria, Sheilla; de Souza Terra, Fábio; Maria Rezende Dázio, Eliza; César do Nascimento, Murilo (Revista Cuidarte, 2021)
Introduction: Cancer is a major public health problem worldwide that has an impact on global morbidity rates. This study aimed to determine the clinical, assistance and epidemiological offer of oncology services provided to people with cancer in a municipality of Minas Gerais, Brazil. Materials and Methods: A descriptive cross-sectional study was conducted with a geographical approach to health using data from oncological medical records in a municipality of Minas Gerais between 2007 and 2017. Epi Info, TerraView and QGIS were used for data analysis. Results: 1914 patients received assistance, who were predominantly white males over 60 years old holding complete elementary education and household occupation. The most frequent clinical care variables included clinical oncology, type I cancer staging, cancer stabilization, skin cancer, adenocarcinoma, surgery, chemotherapy and no reason for non-treatment. An important contribution was observed in records after 2009, as well as a decrease in non-analytic cases. 94.7% of geocoding was made with a heterogeneous spatial offer in urban areas and clusters in different neighborhoods. Conclusions: The clinical, assistance and epidemiological offer proposed for oncology services has actually been carried out. Temporal, spatial and frequency of care offers indicate a substantial increase in healthcare coverage for people with cancer who have received treatment under this scenario. How to cite this article: Ribeiro, Jefferson Felipe; Rodrigues, Denis de Oliveira; Faria, Sheilla de Oliveira; Terra, Fábio de Souza; Dázio, Eliza Maria Rezende; Nascimento, Murilo César do. Configuração dos atendimentos oncológicos em um município de Minas Gerais, Brasil. Revista Cuidarte. 2021;12(1):e1306. http://dx.doi.org/10.15649/cuidarte.1306